A social network based optimal tariff recommender for a group of GSM users - Kaya, Buket; Şener, Abdullah (Institute of Electrical and Electronics Engineers Inc., 2016)
GSM is a mobile technology that allows people to communicate with one another. The technology enables people to call others over the phone with a GSM number and a certain tariff for communication. An interpersonal communication network is established by means of calls and text messages. The purpose of the present study is to develop a system that recommending the most appropriate tariff to each GSM user through social network modelling and thus to consider the total utility of the participants in the communication network. To the best of our knowledge, this is the first study using social network modelling to recommend the most appropriate tariff to a specific group of GSM users. The results of the experiment on a synthetic communication network comprised of users with various tariffs suggest that the method is practical and able to yield accurate results. © 2016 IEEE.
3rd International Conference on Computer and Information Sciences, ICCOINS 2016 -- 15 August 2016 through 17 August 2016 -- Kuala Lumpur -- 125433
Keywords: GSM Tariffs; Recommendation systems; Social networks